A policy-based framework for the determination of management options to protect vulnerable marine ecosystems under the EU deep-sea access regulations. (5th December 2021) - van Denderen, P Daniël; Holah, Helen; Robson, Laura M; Hiddink, Jan Geert; Menot, Lénaick; Pedreschi, Debbi; Kazanidis, Georgios; Llope, Marcos; Turner, Phillip J; Stirling, David; Murillo, F Javier; Kenny, Andrew; et al.
Abstract: Vulnerable marine ecosystems (VMEs) are particularly susceptible to bottom-fishing activity as they are easily disturbed and slow to recover. A data-driven approach was developed to provide management options for the protection of VMEs under the European Union "deep-sea access regulations." A total of two options within two scenarios were developed. The first scenario defined VME closure areas without consideration of fishing activity. Option 1 proposed closures for the protection of VME habitats and likely habitat, while Option 2 also included areas where four types of VME geophysical elements were present. The second scenario additionally considered fishing. This scenario used VME biomass—fishing intensity relationships to identify a threshold where effort of mobile bottom-contact gears was low and unlikely to have caused significant adverse impacts. Achieving a high level of VME protection requires the creation of many closures (> 100), made up of many small (∼50 km 2 ) and fewer larger closures (> 1000 km 2 ). The greatest protection of VMEs will affect approximately 9% of the mobile fleet fishing effort, while closure scenarios that avoid highly fished areas reduce this to around 4–6%. The framework allows managers to choose the level of risk-aversion they wish to apply in protecting VMEs by comparing alternative strategies.